Prospective association of 25(OH)D with metabolic syndrome. (1st April 2013) - Kayaniyil, Sheena; Harris, Stewart B.; Retnakaran, Ravi; Vieth, Reinhold; Knight, Julia A.; Gerstein, Hertzel C.; Perkins, Bruce A.; Zinman, Bernard; Hanley, Anthony J.
Summary Context Vitamin D may play a role in the aetiology of the metabolic syndrome (MetS), yet the majority of previous studies have been cross‐sectional, and the limited number of prospective studies has yielded inconsistent results. Objective To examine the prospective association of vitamin D [25‐hydroxyvitamin D, 25(OH)D] with MetS in a multi‐ethnic cohort of adults in Ontario, Canada. Design Nondiabetic individuals with pre‐existing MetS risk factors were recruited for participation in the PROspective Metabolism and ISlet cell Evaluation (PROMISE) cohort study, a longitudinal study of the determinants of insulin resistance and MetS. Methods Of the 654 participants enrolled at baseline, 489 attended a 3‐year follow‐up visit. There were 301 participants eligible for the analysis of 25(OH)D with incident MetS (age 49·2 ± 9·3 years old, 75·4% female), after excluding 188 (38·5%) prevalent MetS cases at baseline. Longitudinal change in MetS components was assessed in the entire follow‐up cohort. Results There were 76 (15·5%) participants who developed MetS over the 3‐years of follow‐up. Multivariate logistic regression analyses indicated a decreased risk of MetS at follow‐up per standard deviation increase in baseline 25(OH)D after adjustment for sociodemographics, season, baseline and change in supplement use and physical activity and insulin resistance (OR = 0·63, 95% CI 0·44–0·90). Multivariate linear regression analyses revealed a significant inverse association of baseline 25(OH)D with fasting glucose at follow‐up (β = −0·0005, P = 0·025). Conclusions There was a significant inverse association of baseline 25(OH)D with incident MetS, which may be partly driven by its association with glucose homoeostasis.